(untitled) (The Pakistan Development Review, 2015)
Human development is the primary objective of all developing economies of the world. It has great importance in social planning. Every individual, society and nation wants a prosperous life. Different instruments are used, investments are undertaken and different policy frameworks are designed to achieve this target. Human development is a process to enlarge the choices of people. So, the definition of human development is very broad, but people have three basic and essential choices which are acceptable at every level of development. First, people always have desire to live a long and healthy life. Second, they have desire to expand their knowledge. Third, people have desire to access the resources needed for a decent standard of living [UNDP (1990)].